Local and Community Well-Being through Community Based Tourism – A Study of Transformative Eff ect - Baniya, Rojan; Shrestha, Unita; Karn, Mandeep (Journal of Tourism and Hospitality Education, 2018)
Poverty alleviation through community development is well-accepted agenda throughout the globe. One of the recognized tools for such community development endeavors has been community-based tourism. Not only an atecendent of development, community based tourism can have transformative effect on the individual, community and society as a whole, contributing to momentous transformative service movement. This formed the basis of this study. The research focuses primarily in two communities based tourism. Although the research is conducted at two different locations of Nepal, this study’s findings can help guide other similar programs. The findings of the study are encouraging, firstly, it shows CBT can have transformative effect on individual, community and society as a while - people involved in CBT have better individual wellbeing, with satisfaction in their life and better community attachment. In terms of financial wellbeing and psychological needs, CBT seems to fulfill these requirements. Then secondly, it has identified the reasons behind failure of CBT as deficiency in proper mechanism, insufficient scope of coverage, lack of local engagement and empowerment On the positive side, CBT has been successful in stimulating local economy in terms of tourist in flow, enhance the historical heritage, culture, traditions etc., promoting local tradition, generating income promoting local entrepreneurship and produces. The economic impact of CBT is found to be significant. And thirdly based on the outcomes a strong advocacy for CBT is proposed, and this study stands as an attempt to contribute to TSR movement. This research positively links transformative service and community-based tourism together, which has strong future implication. Journal of Tourism and Hospitality Education 8 (2018), page: 77-96